Isolation and Detection of Methicillin-Resistant Staphylococci in Healthy Broilers in Nsukka Southeast, Nigeria - Ifeoma Chinyere UGWU; Madubuike Umunna ANYANWU; Chidozie Clifford UGWU; Jude Chukwuemeka OKORO (Notulae Scientia Biologicae, 2015)
This study was conducted to isolate and detect methicillin-resistant staphylococci (MRS) in healthy broilers in Nsukka Southeast, Nigeria and determine the antibiogram of the isolates. Cloacal and skin swabs were collected from each of 101 randomly sampled broilers meant for slaughter. The samples were processed for isolation and identification of methicillin-resistant Staphylococcus species, following standard methods. Confirmation of methicillin-resistance by the isolates was done using penicillin binding protein 2a (PBP2a) kit. Phenotypic resistance of the isolates to antimicrobial agents was determined using disc diffusion method. Out of 202 samples processed, 200 (99.01%) yielded positive growth of staphylococci on oxacillin-supplemented oxacillin-resistance staphylococcal agar base (ORSAB). A total of 200 methicillin-resistant staphylococcal isolates were obtained. Of these, 91 (45.5%) were identified as methicillin-resistant coagulase-positive Staphylococcus (MRCoPS), while 109 (54.5%) were identified as methicillin-resistant coagulase-negative Staphylococcus species (MRCoNS). Out of the 91 MRCoPS, 53 (58.2%) were identified as methicillin-resistant Staphylococcus aureus (MRSA). Resistance of the isolates was 99.5% to erythromycin and chloramphenicol, 100% to oxacillin, 76.5% to gentamicin, 96.5% to clindamycin, 92.5% to ciprofloxacin, 99% to sulphamethoxazole/trimethoprim and tetracycline, and 98.5% to streptomycin and cefoxitin. All the isolates were multidrug resistant. This study has shown that healthy broilers reared and slaughtered in Nsukka Southeast, Nigeria harbour multidrug-resistant MRS and thus serve as their reservoirs.